Heterogeneous effects of socio-economic status on social engagement level among Chinese older adults: evidence from CHARLS 2020 - Wenjia Li; Xinni Zhang; Han Gao; Qinghe Tang (Frontiers Media S.A., 2024)
IntroductionOlder adults benefit from social connections as it aids in their adjustment to the physical and psychological changes that come with aging, thereby improving their health, well-being, and overall quality of life.MethodsThis study utilizes data from the 2020 China Health and Retirement Longitudinal Study (CHARLS) to investigate the influence of Socio-economic Status (SES) on the social activity levels of older persons and the disparities observed among demographic groups, employing the Heckman two-stage analysis and heterogeneity analysis.ResultsThe results indicate that SES has a significant positive impact on the social engagement of older adults, and this effect varies across different older groups, with women, married individuals living with a spouse, urban residents, those aged 70-79, and individuals with average health conditions.DiscussionTo effectively address the social needs of older adults, it is essential to prioritize integrating cohesive structural methods that improve social connections. Establishing solid and sustainable social support mechanisms and meeting the social needs of older adults across various SES and demographic groups are crucial in promoting active and healthy aging.